Grammatical Ways of Expressing Emotions in English Discourse (Eurasian Research Bulletin, 2022)
The purpose of this article is to discuss national and cultural features of the manifestation of emotions and the means of their expression in various linguistic cultures using the example of the English language and show the need to take into account grammatical means of expressing emotions. Detection and recognition of emotive implicature, i.e. implicit emotive content, which is encoded in the speaker's statement, is a necessary condition for successful intercultural communication and equivalent translation.